Gibberellins control fruit patterning in Arabidopsis thaliana - Arnaud, Nicolas (Cold Spring Harbor Laboratory Press, 2010)
The Arabidopsis basic helix–loop–helix (bHLH) proteins INDEHISCENT (IND) and ALCATRAZ (ALC) specify tissues required for fruit opening that have major roles in seed dispersal and plant domestication. Here, we show that synthesis of the phytohormone gibberellin is a direct and necessary target of IND, and that ALC interacts directly with DELLA repressors, which antagonize ALC function but are destabilized by gibberellin. Thus, the gibberellin/DELLA pathway has a key role in patterning the Arabidopsis fruit, and the interaction between DELLA and bHLH proteins, previously shown to connect gibberellin and light responses, is a versatile regulatory module also used in tissue patterning.